On a Convergence of Formal Power Series Under a Special Condition on the Gelfond-Leont'ev Derivatives - Sheremeta, M.M.; Volokh, O.A. (Журнал математической физики, анализа, геометрии, 2007)
For a formal power series the conditions on the Gelfond-Leont'ev derivatives are found, under which the series represents a function, analytic in the disk {z : |z| < R}, 0 < R ≤ +∞.